2013
DOI: 10.3340/jkns.2013.54.4.309
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Analysis of Intracranial Hemangiopericytoma

Abstract: ObjectiveIntracranial hemangiopericytomas (HPCs) are rare tumors with aggressive behavior, including local recurrence and distant metastasis. We conducted this retrospective study to evaluate the efficacy of grossly total resection and adjuvant radiotherapy (RT) for these tumors.MethodsA total of 13 patients treated for intracranial HPC from January 1995 through May 2013 were included in this retrospective study. We analyzed the clinical presentations, radiologic appearances, treatment results, and follow-up o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
23
1
14

Year Published

2015
2015
2020
2020

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 24 publications
(39 citation statements)
references
References 40 publications
1
23
1
14
Order By: Relevance
“…Therefore, these tumors can occur anywhere where capillaries are found [ 1 10 ]. However, in many reported cases, as well as in our experience, most of intracranial HPCs are located at parasagittal area or at tentorium which is adjoined to the dural sinus [ 2 3 5 6 7 11 12 13 14 15 16 17 ]. Therefore, unless the dural sinus is sacrificed or reconstructed, it is difficult to literally completely remove the tumor in most cases.…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…Therefore, these tumors can occur anywhere where capillaries are found [ 1 10 ]. However, in many reported cases, as well as in our experience, most of intracranial HPCs are located at parasagittal area or at tentorium which is adjoined to the dural sinus [ 2 3 5 6 7 11 12 13 14 15 16 17 ]. Therefore, unless the dural sinus is sacrificed or reconstructed, it is difficult to literally completely remove the tumor in most cases.…”
Section: Discussionmentioning
confidence: 93%
“…Recent studies insist that the extent of surgical resection and postoperative radiotherapy (RT) correlate with improved overall survival (OS) and recurrence-free survival (RFS). However, the definitions of complete resection or grossly total resection (GTR) in previous studies are equivocal [ 5 6 7 8 ]. In most reported cases, since HPC is attached to the venous sinuses or major vessels, it is actually impossible to literally completely remove the tumor.…”
Section: Introductionmentioning
confidence: 99%
“…[3] Park et al in 2013 following their series of 13 patients with CNS HPC reported a mean age of 48 years, with male predominance and majority were located at the parasagittal or falx. [4] The location of intracranial HPCs is similar to that of meningiomas. Like meningiomas and other extraaxial masses, HPCs are dural-based and show white matter "buckling" as was seen in our case.…”
Section: Discussionmentioning
confidence: 95%
“…These tumors are most commonly diagnosed in the fifth decade of life without a clear gender distribution [2,3]. They are indiscriminate in their primary site of origin with the majority of reported cases in the lower extremities, axilla, pelvis, retroperitoneum, and head and neck [2,4].…”
Section: Discussionmentioning
confidence: 99%